The Medial Offshore Record of Explosive Volcanism Along the Central to Eastern Aegean Volcanic Arc: 2. Tephra Ages and Volumes, Eruption Magnitudes and Marine Sedimentation Rate Variations. (23rd December 2021) - Kutterolf, S.; Freundt, A.; Druitt, T. H.; McPhie, J.; Nomikou, P.; Pank, K.; Schindlbeck‐Belo, J. C.; Hansteen, T. H.; Allen, S. R.
Abstract: We use the tephrostratigraphic framework along the Aegean Volcanic Arc established in Part 1 of this contribution to determine hemipelagic sedimentation rates, calculate new tephra ages, and constrain the minimum magnitudes of (sub)plinian eruptions of the last 200 kyrs. Hemipelagic sedimentation rates range from ∼0.5 cm/kyr up to ∼40 cm/kyr and vary laterally as well as over time. Interpolation between dated tephras yields an eruption age of ∼37 ka for the Firiplaka tephra, showing that explosive volcanism on Milos is ∼24 kyrs younger than previously thought. The four marine Nisyros tephras (N1 to N4) identified in Part 1 (including the Upper (N1) and Lower (N4) Pumice) have ages of ∼57 ka, ∼63 ka, ∼69 ka, and ∼76 ka, respectively. Eruption ages for the Yali‐1 and Yali‐2 tephras are ∼55 ka and ∼34 ka, respectively. The Yali‐2 tephra comprises two geochemically and laterally distinct marine facies. The southern facies is identical to the Yali‐2 fall deposit on land but the western facies has slightly less evolved glass compositions. Overall, erupted plinian and co‐ignimbrite fall tephra volumes range from <1 to 56 km 3 (excluding possible caldera fillings and ignimbrite volumes), and 80% of the eruptions had magnitude 5.5 <  M  ≤ 7.2 ( M  = log(m)‐7; m  = erupted magma mass in kg). Twenty percent of the tephras represent 3.2 <  M  < 5.5 eruptions. The long‐term average tephra magma mass flux through highly explosive eruptions of Santorini is estimated at ∼40 kg/s. The analogous data for the Kos‐Yali‐Nisyros volcanic complex is less‐well constrained but similar to Santorini. Plain Language Summary: Sediment cores from the seafloor of the eastern Aegean Sea contain numerous ash layers from (sub)plinian eruptions from the Aegean Volcanic Arc that were correlated in Part 1. These correlations facilitate determination of sedimentation rates of ∼0.5–∼40 cm/kyr within the hemipelagic sediment bracketing the dated tephras. Sedimentation rates show temporal and lateral variations in the context of climate changes, and regional tectonics. Exceptionally high hemipelagic sedimentation rates within the last 4 kyrs, are linked to the 3.6 ka Minoan and the 1650 AD Kolumbo eruptions that emplaced abundant erodible tephra. Using the sedimentation rates we additionally determine the ages of hitherto undated tephras. We deduce an age of ∼37 ka for a Milos eruption, as well as ∼57 ka to ∼76 ka for marine Nisyros and ∼34 and ∼55 ka for Yali tephras, for which previous dating attempts yielded controversial ages. The ash distribution in the marine realm of up to 10 5  km 2 represents a major fraction of the erupted tephra volumes that range from <1 to 56 km 3, placing 60% of the investigated eruptions into magnitude category M6, 20% into M7, and 20% into M3 to M5 classes. Over the past ∼200, 000 years, Santorini discharged magmas at an average rate of ∼40 kg/s. Key Points: Tephrochronology for the Aegean Arc eruptions Sedimentation rate variability in the Aegean Sea Eruptive volumes and masses for the major Aegean Arc eruptions